Correlation study of plaque and gingival indexes of mothers and their children Estudo da correlação dos índices de placa e gengival em mães e filhos - Ana Cláudia Durante Ramires-Romito; Luciana Butini Oliveira; Giuseppe Alexandre Romito; Márcia Pinto Alves Mayer; Célia Regina Martins Delgado Rodrigues (University of São Paulo, 2005)
This study aimed to compare the periodontal condition between plaque and gingival indexes in 30 pairs of mother and child with mixed dentition, as well as to correlate the findings with some of their social and oral hygiene habits. Mother's and child's plaque and gingival indexes were recorded during clinical examination. Periapical and bitewing radiographs were taken in order to assess the presence of any pathologic bone loss. Questionnaires answered by the mothers were used to collect information regarding the mother's and the child's habits of tooth hygiene and the mother's job, instruction level and family income. The data collected from the mothers' group and from the children's group were statistically analyzed both separately and with the two groups together. From the statistical analyses (Pearson correlation test, student test and Covariance analysis), it was possible to conclude that there was a greater correlation between the plaque and gingival indexes in the mothers' group than in the children's group. No significant correlation between plaque and gingival indexes could be found between the pairs. Also, bone loss and plaque and gingival indexes in the children did not show any correlation. The mothers' plaque indexes increased with age and decreased when they flossed everyday and when they had a job. The children's plaque indexes were lower when they had their tooth hygiene done by their mothers, when the latter had declared that they flossed their children's teeth everyday, and also when the mothers had a job. Children's gingival indexes increased with age and decreased when they brushed their teeth more often, when their mothers had a job and when their mothers declared they are used to flossing every day. O objetivo deste estudo foi comparar a condição periodontal em 30 pares de mães e crianças com dentição mista, através dos índices de placa e gengival, bem como verificar sua correlação com alguns aspectos sociais e hábitos de higiene oral. No exame clínico foram registrados o índice de placa (IP) e índice gengival (IG) e, em seguida, foram realizadas tomadas radiográficas periapicais e interproximais que possibilitaram avaliar a possível presença de perdas ósseas em mães e crianças. Através de questionários, foram colhidas informações a respeito dos hábitos de higiene oral das mães e crianças, nível de escolaridade da mãe, se a mãe trabalhava fora e a renda familiar. Após análise estatística (Teste de Correlação de Pearson; test t de Student; Análise de Covariância), concluiu-se que houve maior correlação entre os índices de placa e gengival composto por adultos do que no grupo de crianças. Não foi encontrada correlação significante entre os índices de placa e gengival nos pares de mães e crianças. Não foi encontrada nenhuma correlação significante entre perda óssea e os índices de placa ou gengival dos pares. O índice de placa total das mães aumentou a idade e diminuiu quando a mãe utilizava fio dental diariamente e quando esta trabalhava fora. O índice gengival total das mães também foi reduzido quando elas trabalhavam fora. Houve redução no índice de placa total da criança quando a mãe a auxiliava durante a escovação, quando a mãe utilizava fio dental diariamente e quando esta trabalhava fora. O índice gengival total da criança foi maior com o aumento da idade e foi reduzido com aumento da sua freqüência de escovação, quando a mãe utilizava fio dental diariamente e quando a mãe trabalhava fora.